KEJAHATAN SETAN DALAM AL-QUR’AN - Marzuki, Bakri (State Institute of Islamic Studies (IAIN) Palu, 2005)
Evil is always considered as being identical to satanic deeds. Strength or weakness of satanic domination in human beings are dependent on them. One of the major themes of the Qur’an is satanic evil. In addition, evil is sometimes labeled as iblis or satan. Based on this, this article tries to discuss the existence of satan and to study how the Holy Qur’an gives solution to the satanic treatment.Kata Kunci: Kejahatan, Setan, Manusia, Al-Qur’an, Allah